High Impact Weather Events in the Andes - Poveda, Germán; Espinoza, Jhan Carlo; Zuluaga, Manuel D.; Solman, Silvina A.; Garreaud, René; van Oevelen, Peter J. (Frontiers in Earth Science, 2020)
Owing to the extraordinary latitudinal extent, a strong orographic variability with very high mountain tops, and the presence of deep valleys and steep slopes, the Andes and the population of the region are highly prone and vulnerable to the impacts of a large suite of extreme weather events. Here we provide a review of the most salient events in terms of losses of human and animal lives, economic and monetary losses in costs and damages, and social disruption, namely: (1) extreme precipitation events and related processes (Mesoscale Convective Systems, lightning), (2) cold spells, frosts and high winds, (3) the impacts of ENSO on extreme hydro-meteorological events, (4) floods, (5) landslides, mudslides, avalanches, and (6) droughts, heat waves and fires. For our purposes, we focus this review on three distinctive regions along the Andes: Northern tropical (north of 8˚S), Southern tropical (8˚S-27˚S) and Extratropical Andes (south of 27˚S). Research gaps are also identified and discussed at the end of this review. It is very likely that climate change will increase the vulnerability of the millions of inhabitants of the Andes, impacting their livelihoods and the sustainable development of the region into the 21st century amidst urbanisation, deforestation, air, soil and water pollution, and land use changes.